Aligning agricultural research to meet food security and climate challenges—Bruce Campbell, CGIAR - Campbell, Bruce M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Bruce Campbell, Director of the newly approved 10-year CGIAR research programme on climate change, agriculture and food security (CCAFS), discusses the challenges and opportunities of coordinating the efforts of various agricultural research centres around the world to support food security and climate mitigation and adaptation efforts. Campbell gives an example of Andean seed potato farmers who have had to move to new areas in response to changing weather patterns. He also highlights some of the advances which he hopes will become reality over the lifespan of the CCAFS programme, such as real-time meteorological information being delivered directly to farmers' mobile phones or increased productivity of crops to meet future food demands.